An overview of canopy management in cashew (Anacardium occidentale L.) - D J Adiga (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2020)
Being a tree crop of commercial importance, the productive performance of cashew is greatly influenced by how best its canopy is architectured for harnessing maximum benefits in terms of yield. The initial training is crucial for the development of photosynthetically efficient canopy in cashew as in other perennial fruit trees. Pruning of dead wood and crisscross branches can alone increase the yield by 30-40 per cent. The dwarf rootstocks also play a role in manipulating the canopy in cashew, wherein, canopy containment and yield were influenced by such rootstocks. By resorting to soil application of growth retardants like paclobutrazol, cashew canopy could be successfully contained to suit high density planting system. The studies on planting geometry has indicated the advantage of high density planting in enhancing profitability of cashew orchards in the initial years of plantation. The advantages of rejuvenation as well as top working techniques are also discussed in this  aper.